2014
DOI: 10.1111/pme.12421
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioids for Occupational Injury: Results from Workers' Compensation Claims Records

Abstract: Prescription opioid use for workplace injury in Australia is common but not as common as reports from U.S. workers' compensation schemes. The type of opioid and number of repeat prescriptions are factors that should be carefully considered by practitioners prescribing opioids to injured workers: progression to long-term use is common and not fully explained by injury severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 20 publications
0
33
2
Order By: Relevance
“…A study by Zwisler et al ,24 among Danish population, found that 7.0% of patients with trauma were persistent opioid users 6 months after injuries. Another study examined persistent opioid use among Australian workers and found 6.3% of those injured to be on opioid beyond the first year of injury 25. It is possible that the discrepancy with our findings is due to differences in the study design or, more likely, to prescribing practices between the USA and other countries.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…A study by Zwisler et al ,24 among Danish population, found that 7.0% of patients with trauma were persistent opioid users 6 months after injuries. Another study examined persistent opioid use among Australian workers and found 6.3% of those injured to be on opioid beyond the first year of injury 25. It is possible that the discrepancy with our findings is due to differences in the study design or, more likely, to prescribing practices between the USA and other countries.…”
Section: Discussioncontrasting
confidence: 85%
“…Compared with our result, a higher percentage of persistent opioid use was found among patients with trauma in other countries 24 25. A study by Zwisler et al ,24 among Danish population, found that 7.0% of patients with trauma were persistent opioid users 6 months after injuries.…”
Section: Discussioncontrasting
confidence: 84%
“…In a prior study, we noted an association between the use of short-acting (SA) opioids during the first 60 days postinjury and increased workers' compensation costs and delayed return to work. 9 However, Berecki-Gisolf et al 6 reported that opioid use, limited to the first 2 weeks post injury, was not associated with prolonged time out from work. This suggests that the use of opioids to treat the acute pain associated with an injury would not necessarily lead to prolonged disability durations or increased costs.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6] Prescribing opioid medications for greater than 7 days during the first 6 weeks postinjury or receipt of more than one opioid prescription in that time period is associated with increased disability at 1 year postinjury. 3 Other studies have noted an association between receipt of opioid prescriptions within the first 2 weeks postinjury and longer disability durations.…”
mentioning
confidence: 99%
“…85 Similar numbers are reflected in the nonoccupational setting 16,17,142 Occupational medicine guidelines do not support extensive use of opioids, and according to a review by the American Pain Society and the American College of Physicians, opioids have not been shown to be superior to placebo for conditions such as acute LBP in any RCTs. 16,17 A cross-sectional study in Canada revealed that higher doses of morphine (>120 MED) are associated with workers’ compensation patients than the general population (OR = 2.06; 95% CI: 1.58 to 2.69).…”
Section: Resultsmentioning
confidence: 99%